An analysis of the mathematical competencies needed for success in machine shop practice - So, Emiliano Facundo 1946- (1975)
Mathematical skills and processes that are necessary for success in Machine Shop Practice are determined in the study. The fundamental operations: addition, subtraction, multiplication and division; applications of geometry and trigonometry, and those involving ratio and percentage are identified to be the skills significant in Machine Shop Practice.
Thesis (M.A.T.)--University of the Philippines
Keywords: Vocational education -- Philippines; Mathematical ability